The knowledge contract : politics and paradigms in the academic workplace - Downing, David B., 1947- (University of Nebraska Press, 2005)
"The Knowledge Contract intervenes in the ongoing debates about the changing conditions of higher education in America, with a special focus on English studies and the humanities. This highly original study integrates three crucial concerns: the economic restructuring of higher education, the transformation of disciplinary models of teaching and research, and the rise of the academic labor movement." "Whereas most contemporary critiques of higher education have focused on the impact of global economic forces, The Knowledge Contract adds a new dimension to the discussion by addressing the tensions between disciplinary and nondisciplinary forms of academic work."--Jacket